Tumor Metastasis to the Liver, and the Roles of Proteinases and Adhesion Molecules: New Concepts from In Vivo Videomicroscopy - Alan C Groom; Ian C MacDonald; Eric E Schmidt; Vincent L Morris; Ann F Chambers (Canadian Journal of Gastroenterology)
Most preclinical studies of tumour metastasis and effects of molecular interventions have been based on end point assays, and little is known about the fate of cells at sequential steps in the metastatic process. In vivo videomicroscopy permits direct observations of sequential steps in hematogenous metastasis as they occur in living animals over time. These steps include initial arrest of cells in the microcirculation, extravasation, postextravasation migration and growth in the target organ. In the mouse liver model, cells are arrested in periportal sinusoids based on size restriction, survive in the circulation and extravasate into the tissue by 48 to 72 h regardless of metastatic potential. Thereafter, cells may migrate to preferred sites for growth. Critical steps responsible for cell losses and metastatic inefficiency occur at the level of postextravasation cell growth. Many extravasated cells may remain dormant, and growth to form micrometastases is initiated in only a small subset of cells. Most early micrometastases may disappear after a few days, and only a small subset continue growth into macroscopic tumours. Angiogenesis is a prerequisite for continued growth of metastases, as shown previously by others. Integrin-based interventions can modulate postextravasation cell migration and cell growth. Matrix metalloproteinase inhibitors can inhibit tumour angiogenesis and thus reduce growth. Key targets against which future therapeutic strategies should be directed include the initiation and maintenance of growth of micrometastases, and the activation of dormant solitary cells.